Thiohydrazides in the Synthesis of Functionalized Extranuclear Heterosteroids - Yulia Volkova; Alexander Scherbakov; Igor Zavarzin (Chemistry Proceedings)
Heterocyclic derivatives of hormones have attracted great interest as a privileged scaffold for drug discovery due to their outstanding biological activity. A number of them are potent anticancer agents which are used in the chemotherapy of breast and prostate cancers. Here, the data obtained by the authors in the field of studying functionalized thiohydrazides as simple “versatile agents” for the installation of heterocyclic moiety to the steroid core are summarized. Namely, a flexible synthetic approach to unknown pyrazolines, 1,3,4-thiadiazole, thiadiazine, and pyridazine derivatives of steroids with selective control of heterocyclization patterns are discussed. Steroidal 1,3,4-thiadiazoles were obtained via the oxidative heterocyclization of oxamic acid thiohydrazides with 16-hydroxymethylidene-∆1,3,5(10)-estratrieno-17-one. An extension of this reaction to steroidal α,β-unsaturated ketones resulted in androst-5-ene-[17,16d]-pyrazolines. Spiro-androstene-17,6′[1′,3′,4′]thiadiazines were exclusively synthesized employing 16β,17β-epoxypregnenolone. Using 21-bromopregna-5,16-dien-20-one as a substrate, 17-[1′,3′,4′]thiadiazine-substituted androstenes were prepared. 18-Nor-5α-androsta-2,13-diene[3,2-d]pyridazines, androsta-2-ene[3,2-d]pyridazines and ∆1,3,5(10)-estratrieno[16,17-d]pyridazines were synthesized via two steps involving the Vilsmeier–Haack reaction of enolizable steroidal ketones, giving chlorovinyl aldehydes, followed by the imination of the former with oxamic acid thiohydrazides. The antiproliferative activity of the synthesized compounds against breast and prostate cancer cell lines, along with lead compounds’ in-depth characterization, are included. The lead compounds were found to have potent selectivity and, in some cases, a significant effect on the signaling pathways in parental and 4-hydroxytamoxifen-resistant cells.